Corporal mass index and body image perception by women attending at health and physical activity office of "Raúl Sánchez" polyclinic - Dianelys Ledesma-Beades; Noemí Roig-Méndez; Mireya Contino-Torres (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2015)
The corporal image is the mental representation of the body that each individual builds. The dissatisfaction with the image and the corporal mass is closely associated to the self-esteem of the women. According to researches there are many concerned and insecure women in relation to their own shapes with a high index of corporal dissatisfaction, constituting a world problem. A high index of women goes to the physical activity and health consultation that Raúl Sánchez policlinic of Pinar del Río; offers many of them, for their dissent with the corporal weight. For this reason, we decide to carry out a research with the objective of determining the existent relationship between the CMI and the perception of the corporal image in women that attend to this consultation during the year 2014. It is a descriptive transverse study with a sample of 102 women older than 15 years old. They were carried out measured (weigh corporal and stature) and a questionnaire was made to establish the grade of corporal dissatisfaction. It was used the questionnaire proposed by Stunkard, constituted by ten silhouettes for the feminine gender, numbered and ordained for the selection of one of them, that according to her perception and pleasure, it corresponded to her current corporal image and to how they wanted to be. The obtained data were tabulated and represented by means of charts. It was concluded that a high percent of these women is perceived incorrectly: 0,98% is undernourished and 62,8%, fatter; that the women with values of real CMI corresponding with normal weight and overweight are fatter than they really are, while the obese ones are perceived thinner; they consider that the pregnancies have been the main cause of the changes in the corporal weight and their grade of corporal dissatisfaction is based on 70,6% by their appearance before the society.